Organizational Assimilation of Collaborative Information Technologies: Global Comparisons - Bajwa, D.; Pervan, Graham; Munkvold, B.; Lewis, L.; Lai, V.; Schwabe, G. (IEEE, 2007)
This paper reports on a global initiative to investigate the assimilation of collaborative information technologies (CITs) in task-oriented collaboration. The two classes of CITs explored include conferencing and groupware technologies. Based upon the level of technology access/availability and utilization, four assimilation states are identified. Data collected from 538 organizations in the US, Australia, Hong Kong, Norway, and Switzerland is mapped in the four CIT assimilation states. The resultsindicate that the assimilation patterns of conferencing and groupware technologies vary across the study regions. Overall analyses of the organizational antecedents of CIT assimilation indicate that function integration and promotion of collaboration aresignificantly associated with the assimilation of conferencing and groupware technologies. Organization size and information technology (IT) function size, on the other hand, were found to be significantly associated only with the assimilation ofconferencing technologies. Implications of our findings are discussed for practice and research.